Proses pemijahan semi buatan dengan teknik stripping (pengurutan) pada ikan Betok (Anabas testudineus) - Tania Serezova Augusta; Deby Setyani; Fitri Riyanti (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2020)
Climbing gouramy or Climbing perch (Anabas testudineus) is one freshwater fish species which of high economic value. The Climbing gouramis has the potential to be developed as an alternative food nutrition, when the environmental conditions are less supportive of aquaculture result pollotion as well as extreme conditios. The climbing gouramis spawning by the artificial stripping technique is one of alternative to increase of cultivation productivity. The fish spawning is by provided ovaprim hormone stimulation to accelerate gonad maturity, ovulations are by stripping technique. Based on the evaluation and monitoring at Balai Benih Ikan Sei Batang Kuala Kapuas with active participation out directly to fish spawning, the activities has several stages that are 1). Countainer preparation 2). Main selection 3). Pemberokan 4).Spawning 5). Treatment of larva. This activity is able to provide insight and knowledge as informations for the whole community on the spawning fish with artificial techniques. Keywords : Climbing gouramy/Climbing perch, spawning, stripping.